Action-level real-time DEVS modeling and simulation. (October 2015) - Sarjoughian, Hessam S; Gholami, Soroosh
For some classes of systems, it is advantageous to develop real-time models instead of step-wise or logical-time models. Toward this goal, the action-level real-time (ALRT) discrete-event system specification (DEVS) modeling and simulation approach is proposed. Modeling of actions is introduced into the parallel DEVS formalism using time invariants defined for real-time statecharts. Actions are specified in terms of time-windows that are to be executed in real-time. An abstract simulator protocol is devised for executing the ALRT-DEVS models under constrained computational resources. The approach is implemented in the parallel DEVS-Suite simulator. These models can be simulated on unitary computing platforms. A simple example switch model is detailed and tested to show the kinds of real-time modeling and simulation studies that can be supported.